Anti-cancer activity of rutin encapsulated in low methoxyl pectin beads - Pensak Jantrawut (2018)
Objective: This study was investigating the anti-cancer activity of rutin encapsulated in non-amidated low methoxyl pectin bead in various formulations with or without sorbitol and/or sodium bicarbonate (NaHCO 3 ).Methods: The rutin beads formulations including 3NA (3% Non-amidated LMP), 3NA15Sor (3% Non-amidated LMP with 15% Sorbitol), 3NA1Bica (3% Non-amidated LMP with 1% NaHCO3) and 3NA15Sor1Bica (3% Non-amidated LMP with 15% Sorbitol and 1% NaHCO 3 ) were prepared and the in vitro anti-cancer activities in 3 human cancer cell lines were investigated. Results: All beads were oblong or spherical shape with around 600 μm size. 3NA15Sor1Bica rutin bead composing both sorbitol and NaHCO 3 exhibited higher cytotoxic activity with cancer cell viability were 51.41 ± 7.01 and 55.12 ± 3.96% on HT-29 and KB cells, respectively. There was no significant different (p > 0.05) of cell viability between all bead formulation for HepG2 cells. Conclusion: These results confirmed that encapsulation of rutin in pectin beads exhibited their anti-cancer activity and can be applied for further human cancer treatment formulation.